Lactate testing for swim coaches
Lactate testing has been used by Olympic Champions and World record-holders for over twenty years. These pages will explain the testing methods of lactate analysis and the interpretation of results - probably the least understood, yet most important, aspect of lactate testing. Our goal is to provide you with all the necessary information and knowledge to develop, maintain and enhance the performance characteristics of your swimmers.